2016
DOI: 10.3390/molecules21081016
|View full text |Cite
|
Sign up to set email alerts
|

Preparative Separation of Phenolic Compounds from Chimonanthus praecox Flowers by High-Speed Counter-Current Chromatography Using a Stepwise Elution Mode

Abstract: High-speed counter-current chromatography (HSCCC) has been successfully used for the separation of eight compounds from Chimonanthus praecox flowers. Firstly, the crude extract of Chimonanthus praecox flowers was dissolved in a two-phase solvent system composed of petroleum ether-ethyl acetate-methanol-H 2 O (5:5:3:7, v/v) and divided into two parts: the upper phase (part I) and the lower phase (part II). Then, HSCCC was applied to separate the phenolic acids from part I and part II, respectively. Considering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
0
25
0
1
Order By: Relevance
“…In other words, 12 target compounds could not be separated using a single solvent system. To overcome this problem and simultaneously separate compounds with largely different K values, stepwise HSCCC elution mode was proposed [27].…”
Section: Resultsmentioning
confidence: 99%
“…In other words, 12 target compounds could not be separated using a single solvent system. To overcome this problem and simultaneously separate compounds with largely different K values, stepwise HSCCC elution mode was proposed [27].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, HSCCC has been widely used for the separation and purification of active components from natural products, albeit, it is a big challenge to separate all target components directly from crude extract in a single run. Therefore, the stepwise elution mode was introduced into HSCCC separation to address this problem . The common gradient modes used in counter‐current chromatography (CCC) include temperature gradients, stepwise flow‐rate gradients, stepwise solvent gradients, pH‐gradients, and salting‐out gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the stepwise elution mode was introduced into HSCCC separation to address this problem. [18][19][20] The common gradient modes used in counter-current chromatography (CCC) include temperature gradients, stepwise flow-rate gradients, 21,22 stepwise solvent gradients, 20,23 pH-gradients, and salting-out gradients. However, few articles related to HSCCC separation of natural products reported the combination of these gradient modes.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have revealed that dipeptides and phenolics—which exhibited various pharmacological activities—are the main active ingredients of this drug [ 5 ]. As part of our continuous work on the systematic study of this insect, the chemical constituents of B. rynchopetera was investigated to afford five new phenolic compounds rynchopeterines A–E ( 1 – 5 ) ( Figure 1 ), along with thirteen known phenolics, procatechuic acid ( 6 ) [ 6 ], 3,4-dihydroxyphenylacetic acid ( 7 ) [ 7 ], 3,4-dihydroxybenzaldehyde ( 8 ) [ 8 ], 3,4-dihydroxyphenylacetaldehyde ( 9 ) [ 9 ], methyl 3,4-dihydroxybenzoate ( 10 ) [ 10 ], 3,4-dihydroxyphenylacetic acid methyl ester ( 11 ) [ 11 ], 3,4-dihydroxyphenylacetic acid ethyl ester ( 12 ) [ 7 ], 2-(3,4-dihydroxyphenyl)ethanol ( 13 ) [ 12 ], 3,4-dihydroxyphenethylacetate ( 14 ) [ 13 ], blapsins A ( 15 ) and B ( 16 ) [ 14 ], 1-(3,4-dimethoxyphenyl)-4-hydroxypentan-1-one ( 17 ) [ 15 ], and 3,3′,4,4′-tetrahydroxybiphenyl ( 18 ) [ 16 ] (see Supplementary ). Herein, the isolation, structural elucidation, and bioactivity of the new compounds are described.…”
Section: Introductionmentioning
confidence: 99%